Microplastics, microfibres and nanoplastics cause variable sub-lethal responses in mussels (Mytilus spp.). (November 2020) - Cole, Matthew; Liddle, Corin; Consolandi, Giulia; Drago, Claudia; Hird, Cameron; Lindeque, Penelope K.; Galloway, Tamara S.
Abstract: We compare the toxicity of microplastics, microfibres and nanoplastics on mussels. Mussels (Mytilus spp.) were exposed to 500 ng mL-1 of 20 μm polystyrene microplastics, 10 × 30 μm polyamide microfibres or 50 nm polystyrene nanoplastics for 24 h or 7 days. Biomarkers of immune response, oxidative stress response, lysosomal destabilisation and genotoxic damage were measured in haemolymph, digestive gland and gills. Microplastics and microfibres were observed in the digestive glands, with significantly higher plastic concentrations after 7-days exposure (ANOVA, P < 0.05). Nanoplastics had a significant effect on hyalinocyte-granulocyte ratios (ANOVA, P < 0.05), indicative of a heightened immune response. SOD activity was significantly increased followed 24 h exposure to plastics (two-way ANOVA, P < 0.05), but returned to normal levels after 7-days exposure. No evidence of lysosomal destabilisation or genotoxic damage was observed from any form of plastic. The study highlights how particle size is a key factor in plastic particulate toxicity. Graphical abstract: Unlabelled Image Highlights: Mussels ( Mytilus edulis ) exposed to micro- and nanoplastics for 24 h and 7 days. Microplastics and microfibres aggregated in the digestive glands. Plastic exposure caused a short-lived increase in SOD activity. Nanoplastics triggered an innate immune response.